Reconstructing the Epistemology of Islamic English: Ismail R. Al-Faruqi’s Framework for the Islamization of Language - Amir, Ahmad Nabil; Rahman, Tasnim Abdul; Sukron, Mokhamad (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
The paper highlights Ismail Raji al Faruqi’s (1339-1406 H/1921-1986 M) seminal work, Toward Islamic English that outline general ideas and framework of Islamization of English language by reconstructing its ontological and epistemological premises to align it with tauhid and its metaphysical worldview in the context of Islam. Its objective is to analyzes his method that provided constructive analysis of the nature of linguistic distortion of the English language that needed rectification in transliteration (of letters and words) and translation (of Islamic words/concepts and terms/expressions relevant to the Islamic sciences). The study is qualitative (narrative) in nature based on descriptive, analytical and historical method. The finding reveals certain major pattern of Islamicization of language at work designed to inject into it new vision and new spiritual sensitivities and dismantle its secular premise and its overarching presence in its worldview and consciousness. It strives to enrich the English language and attempts to modify it to allow it to carry Islamic proper nouns and meanings without distortion, and thus to serve the linguistic needs of Muslim users of the English language